Non-systemic opposition in authoritarian regimes : Alexei Navalny case in Russia - Emer, Furkan (My University, 2022)
Günümüz otoriter rejimlerinde siyasal muhalefet, hükümet onu baskıladığı için can çekişen bir türdür. Muhalefetin ve otoriter rejimlerin güncel örneklerini geleneksel literatür ile açıklamak zordur. Bu gibi örneklerin iki tanesi hibrit rejimler ve sistem-dışı muhalefetlerdir. Bu çalışma bir hibrit rejim örneği olarak Rusya’ya ve bu yönetim biçiminde yaşayan bir sistem-dışı muhalefet örneği olarak Aleksey Navalni’ye odaklanır. Dahası; Alfred Stepan’ın, karşı çıktığı otoriter yönetimi demokratikleştirmek için siyasal muhalefete beş ödev önerdiği teorik sistemi, bu incelemeye analitik araçlar sağlamaktadır. Bu analitik yaklaşım, siyasi kariyeri boyunca Putin rejimine güvenilir demokratik bir alternatif yaratıp yaratmadığını test etmek için Aleksey Navalni vakasına uygulanmıştır. Bulgular, Navalni’nin başarılı bir şekilde otoriter yönetimin maliyetini yükseltmesine rağmen Rus hükümetine karşı çıkma şeklinin demokratik olmadığını göstermektedir.

Political opposition is a moribund species in contemporary authoritarian regimes since the government pressures it by the state apparatus. It is difficult to explain the current versions of oppositions and authoritarian regimes with the traditional literature. Hybrid regimes and non-systemic oppositions are two of such versions. This study focuses on Russia as an example of a hybrid regime and Alexei Navalny as a non-systemic opposition living in this polity. Moreover, Alfred Stepan’s theoretical framework in which he proposes five tasks for the political opposition to democratize the authoritarian rule it opposes provides analytical tools for this examination. This analytical approach has implemented in the case of Alexei Navalny to test whether he has created a credible democratic alternative to Putin’s regime throughout his political career. The findings suggest that although Navalny has successfully raised the costs of the authoritarian rule in Russian politics, his way of opposing against the Russian government is undemocratic.
Keywords: Aleksey Navalni; Alexei Navalny; Alfred Stepan; authoritarian regimes; democratization; demokratikleşme non-systemic opposition; International relations; otoriter rejimler; Political science; sistem-dışı muhalefet; Siyasal bilim; Uluslararası ilişkiler